Students’ and lecturers’ perceptions of the effect of open-book examinations on teaching and assessment at departments of accountancy at South African universities - Kruger, S.J. (South African Journal of Higher Education, 2019)
Strong arguments are put forward in literature that teaching methods should be aligned with assessment practices in order to optimise the teaching-learning environment. The decision by the South African Institute of Chartered Accountants to change its qualifying examination from a closed-book to an open-book format has led to accredited universities changing their assessment accordingly. This paper investigates how students and lecturers perceive the changes made to teaching and assessment after the introduction of open-book assessment. A survey was performed among final-year accounting students preparing for the qualifying examination of the South African Institute of Chartered Accountants. Assessment in the first three years of study of these students was generally done by means of closed-book examinations, but in their final year, students were assessed by means of open-book tests and examinations. A comparison was made between the views of students and lecturers in certain universities’ departments of accountancy. The views of students and lecturers differed significantly on the extent of changes which were made to teaching practices and the setting of examination papers. The paper identified aspects to be considered to encourage students’ deep learning, long term retention, selection of knowledge and preparation for open-book assessment. Issues lecturers need to take into account when determining their teaching and assessment approach within the broader context of an open-book assessment environment were also identified.